1927
DOI: 10.1042/bj0210665
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Significance of Hexosephosphoric Esters in Ossification

Abstract: IN the earlier papers of this series [Robison and Soames, 1924] some account was given of the properties of the phosphatase which is present in ossifying cartilage, bones and teeth, and also in the kidney and intestinal mucosa. In the following we give the results of a more detailed study of some of its properties about which further knowledge was desirable in order to understand the part played by this enzyme and by phosphoric esters in the process of ossification. OPTIMUM PH. It was previously stated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1932
1932
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…4. Effect of long incubation on phosphomonoesterase in TC with both enzymes (at pH 5 and 10.9 respectively) and may be due to the inactivation of the phosphatase as effect of pH (33). Assays of long term incubation also gave comparable results but the rate of alkaline phosphatase activity was markedly reduced in normal 14 day old cultures.…”
Section: Eject Of Time and Temperature Of Incubationsupporting
confidence: 55%
See 1 more Smart Citation
“…4. Effect of long incubation on phosphomonoesterase in TC with both enzymes (at pH 5 and 10.9 respectively) and may be due to the inactivation of the phosphatase as effect of pH (33). Assays of long term incubation also gave comparable results but the rate of alkaline phosphatase activity was markedly reduced in normal 14 day old cultures.…”
Section: Eject Of Time and Temperature Of Incubationsupporting
confidence: 55%
“…The inhibition may be the primary change and precedes the visible CPE for days, depending on the size of inoculum. Any phosphatase method (16,18,34,33) could be adopted for the purpose of measuring enzyme activities in roller tubes or large production bottles (15).…”
Section: Discussionmentioning
confidence: 99%
“…This fact was first recognized in the 1920s when Martland and Robison stated that the function of alkaline phosphatase was to increase the local phosphate concentration [59]. Later in the 1970s Binderman et al found that elevating phosphate levels was sufficient to convert a non-mineralizing differentiating mesenchymal cell culture that formed cartilage into one that formed calcified cartilage [60].…”
Section: The Importance Of Local Phosphate Concentrationsmentioning
confidence: 97%
“…of investigations on the isolation, the mode-of-action and the distribution of phosphoric esterases in different tissues [4][5][6][7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%